Comparative proteomic analyses of two reovirus T3D subtypes and comparison to T1L identifies multiple novel proteins in key cellular pathogenic pathways. Issue 12 (26th May 2015) - Berard, Alicia R.; Severini, Alberto; Coombs, Kevin M.; Cristea, Ileana M.; Graham, David
<x xml:space="preserve">Abstract</x> Viruses induce changes in the host to facilitate replication and evade the immune response. These changes are reflected by the host's proteome, including differences in protein abundance. Focusing on up and down regulated proteins after a virus infects the cell will lead to a characterization of the host response to infection, and may give insight into how viruses modulate proteins to evade host defense responses. We previously used SILAC to examine host proteomic changes in protein abundance in HEK293 cells infected with reovirus type 1, strain Lang (T1L). For the present study, we extended this analysis by determining cell protein alterations induced by two different reovirus subtypes, a less pathogenic type 3 Dearing (T3DF) isolate, and a more pathogenic isolate named T3DC that is presently in clinical trials as an anti‐cancer oncolytic agent. This comparison of host proteome regulation showed that T3DC had a more marked effect on DNA replication proteins, recombination and repair, as well as immunological, apoptotic, and survival cell functions. We also identified several proteins not previously identified in any virus infection; branched chain amino‐acid transaminase 2 (BCAT), paternally expressed 10 (PEG10), target of myb1 (TOM1), histone cluster 2 H4b (HIST2H4B) and tubulin beta 4B (TUBB4B).